2017
DOI: 10.1017/s002185961700079x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer value and greenhouse gas emissions from solid fraction pig slurry compost pellets

Abstract: 19Conversion of pig slurry to pellets is a desirable fertilizer option for farmers who want to 20 mitigate environmental pollution from slurry accumulation. The goals of the current 21 investigation were to determine the fertilizer properties of pig slurry solid fraction (SF) pellets 22 and to assess its potential to enhance soil properties in order to reduce ammonia (NH3) 23 volatilization and greenhouse gas (GHG) emissions. Various parameters influence SF-24 based pellet fertilizer effectiveness: bulking age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…In addition, the non-industrial food waste compost had the highest concentrations of resin P. This confirms the greater fertilizer value of food-based composts compared to cow manure-based composts, as food waste is high in N and P, e.g., 3% N and 0.41% P in Graunke and Wilkie [33], whereas screened manure solids are high in fiber and low in nutrients [23]. Despite these properties, other manure solid products may provide more fertility than the ones tested in this study, such as solid fraction pig slurry compost pellets that can provide similar N availability as mineral fertilizers [19].…”
Section: The Effects Of Feedstock and Composting Processmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the non-industrial food waste compost had the highest concentrations of resin P. This confirms the greater fertilizer value of food-based composts compared to cow manure-based composts, as food waste is high in N and P, e.g., 3% N and 0.41% P in Graunke and Wilkie [33], whereas screened manure solids are high in fiber and low in nutrients [23]. Despite these properties, other manure solid products may provide more fertility than the ones tested in this study, such as solid fraction pig slurry compost pellets that can provide similar N availability as mineral fertilizers [19].…”
Section: The Effects Of Feedstock and Composting Processmentioning
confidence: 82%
“…Compost processing conditions also increase variability among composts, as composting duration, oxygen availability, moisture [17], and additional processing (e.g., vermicomposting, pelletization) affect nutrient content and other properties [18,19]. These conditions vary considerably among operations, although industrial composting facilities reduce this variability with streamlined protocols that produce a more consistent and stable product [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that the application of soil organic amendments could increase the persistence of herbicides by increasing the sorption process (Barker and Bryson 2002;Wanner et al 2005). Different studies showed that the addition of organic matter including manures, composts, and plant residues to soils is a widely accepted non-chemical approach for improving the soil characteristics as well as the different crop production (Garcia-Gomez et al 2002;Perez-Murcia et al 2006;Bastida et al 2008;Mehdizadeh et al 2013;Pampuro et al 2017a). Cox et al (2000) concluded that the infertile soils had a minimum effect on herbicide movement; therefore, the presence of organic matter can be considered as an important adsorbent for herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…Despite knowledge of the benefits related to composted animal manure's application on soil quality [19,20], soil fertility [21][22][23], and the environment [24,25], this material was increasingly considered as a waste in the Mediterranean regions of Europe [26]. With reference to Italy, application of composted manure is not a common practice [23].…”
Section: Introductionmentioning
confidence: 99%
“…With reference to Italy, application of composted manure is not a common practice [23]. In this specific geographic area, slurry storage for subsequent land application is the predominant manure management practice, probably due to its simplicity and low cost [23]. However, this technique carries several environmental pollution risks, such as ammonia and greenhouse gas emissions into the atmosphere, nitrate leaching into groundwater, and phosphorous runoff into surface waters [20,27,28].…”
Section: Introductionmentioning
confidence: 99%